SIMPEets Operating Manifesto – Pediatric action in adolescence - Maria Giuliano; Giuseppe Squazzini; Nicola D’Amario; Roberto Sassi; Cristiano Rosafio; Luigi Bresciani; Giampiero Mele; Francesco De Luca; Antonella De Vito; Giuseppe Mele (Journal of Pediatric and Neonatal Individualized Medicine, 2025)
ENGLISH TEXT: Adolescence is a complex and change-filled transition phase, in which young people face challenges related not only to personal growth, but also to an increasingly pressing and hyperconnected social context. Often criticized by adults, adolescents hide a rich and vulnerable inner world that needs to be listened to rather than judged. They are no worse or better than previous generations, but they live in different times, which amplify their fragility and potential. In this scenario, pediatricians play a fundamental role in promoting physical and mental well-being, preventing distress, and supporting identity building. This awareness has led to the SIMPEets Operational Manifesto – Pediatric action in adolescence, promoted by SIMPEets (Italian Society of Pediatricians, Third Sector Organization, Società Italiana Medici Pediatri, Ente del Terzo Settore), which proposes 11 concrete actions to strengthen the role of pediatricians as active and present figures in the everyday lives of adolescents. Accompanying, rather than correcting, is the key to supporting adolescents toward a possible future.